Diseño de un plan de mantenimiento, basado en la cargabilidad y análisis de resultados termográficos predictivos, para las subestaciones de la Unidad de negocio Bolívar. - Mosquera Velásquez, Fabricio Ismael (2018)
This work research "DESIGN OF A MAINTENANCE PLAN BASED ON THE CHARGABILITY AND ANALYSIS OF PREDICTIVE THERMOGRAPHIC RESULTS FOR THE SUBSTATIONS AT BOLÍVAR BUSINESS UNIT” deals with the thermographic analysis in the Electric Substations of the EPC Unit Bolívar business with the purpose of determining hot spots, which serve for the evaluation of predictive maintenance and thus reduce the number of interruptions to users. Within the development of the current investigation, a technical sheet is designed for the collection and subsequent analysis of the thermographic images of the respective anomalies found, to describe in a timely manner each of the causes and their respective solutions in accordance with the ANSI / NETA standard ATS-2009, which will allow the proposal of a predictive maintenance plan based on the period evaluated. Finally, an economic analysis, conclusions and recommendations that allow the Cnel. EP Business Unit Bolívar decrease the interruptions of electric service to improve the quality indexes of the company.